The Influence Of Emotional Intelligence and Parenting Styles On The Resilience Of Students At SMK Tirta Sari Surya - Lestari, Diah Indah; Kartikowati, Rr. Sri; Maulida, Ervina (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
The objectives of this research are 1) to determine the effect of emotional intelligence on the resilience of students at SMK Tirta Sari Surya. 2) to determine the effect of parenting styles on the resilience of students at SMK Tirta Sari Surya. 3) to determine the effect of emotional intelligence and parenting styles on the resilience of students at SMK Tirta Sari Surya. This study utilizes a quantitative approach with a survey method. The population for this research consists of 518 students from SMK Tirta Sari Surya. The samples were obtained using the proportionate stratified random sampling method, resulting in a total of 225 students for this research. The data collected was then analyzed using SEM-PLS (Structural Equation Model – Partial Least Square) with data processing utilizing the SmartPLS 4.0 software. The data analysis techniques in this study include measurement model analysis, structural model analysis, and hypothesis testing. The results of this research indicate that are 1) there is a positive and significant effect between emotional intelligence on resilience. 2) there is a positive and significant effect between parenting styles on resilience. 3) there is a positive and significant effect jointly between emotional intelligence and parenting styles on resilience.